O sujeito educando da EJA e a cidade: um estudo sobre as mudanças provocadas pela reinserção na escola - Suellen Guimaraes Alves (2017)
The aim of this research was to understand if, and how, the admission in Program of Youth and Adult Education of UFMG modifies the relation of the students with the city. Based on the researches in the field of Youth and Adult Education (Educação de Jovens e Adultos - EJA) that seek to understand the studenst´s perceptions about the continuation of the schooling process and the possible changes that it can provoke, interviews were conducted with six students enrolled in the "Project of High School for Youth and Adults" (Projeto de Ensino Médio de Jovens e Adultos - PEMJA) and in the "Project of Elementary Education for Youth an Adults" (Projeot de Ensino Fundamental de Jovens e Adultos - PROEF-2). The production of the data also ocurred through the observation of activities developed in spaces outside the school, mediated by the teachers. Since the insertion in EJA, some changes have occurred, such as the willingness socialize with others, openness to risk, the creation of affective bonds, the expansion of networks of relations and the development of the capacity of affective bonds, the expansion of networks of relations and the development of the capacity of self-expression in different situations and environments. These changes focused on how these individuals relate to the city. The expansion of networks of relations and the creation of new ties allowed the diversification of the modes of using free time outside the domestic environment. The gained security in putting oneself in public allowed the access to places "obstructed" or restricted until then. From activities outside the school, they had the opportunity to live a "time for themselves", to know and occupy spaces that until then qere not part of the repertoire of possibilities of uses of the city. The difficulty of access to information, the feeling of internalized inferiority, the lack of time, resources and company appear as barriers to new appropriations. However, the expansion of the network of relations appears as a great facilitator. there are also remarks about the emergence of a new look at the socially produced space, more critical and more attentive to social transformations and inequalities. Regarding the relation between the students and the Pampulha campus, despite the restricted access and circulation in areas other than the school and the university restaurant, the students take over the social prestige conferred to the university, evem partially and through an extra-mural activity. "Studying at UFMG", besides being a great reason for pride, appears as an incentive of permanence, since they consider a stimulating environment for studying.